Audit Education For Future Professionals: Insights From Auditors In Vietnam - Doan Nguyen Trang, Phuong (The International Journal of Accounting and Business Society, 2026)
Purpose:This study examines the audit topics, professional skills, pedagogical approaches, and disciplinary knowledge that practicing auditors in Vietnam perceive as most important for preparing undergraduate audit students. The objective is to identify areas of alignment and mismatch between university audit curricula and professional expectations in a rapidly developing economic context. Methodology:A structured questionnaire comprising 72 items was developed and pilot-tested with auditors and accounting educators. The survey was administered to professional auditors working in Danang, Vietnam, resulting in 84 valid responses. Data were analyzed using descriptive statistics and non-parametric tests, including Chi-square and Kruskal–Wallis analyses, to explore differences in perceptions across experience levels, job functions, and firm types. Findings:The results indicate strong practitioner emphasis on judgment-oriented audit topics, particularly risk assessment, audit planning, independence, and professional ethics. Complex areas such as fraud detection and the formulation of audit opinions were viewed as more effectively taught by experienced practitioners than through traditional classroom instruction. Core skills related to document examination, preparation of working papers, teamwork, and client communication were consistently prioritized. Respondents expressed a preference for technology-supported learning activities, including audit simulations and analytical review exercises, while resource-intensive teaching methods (e.g., role-playing, videos, and office visits) were perceived as less effective. Statistically significant differences were observed across auditor characteristics, and knowledge of IFRS, accounting practice, and data analysis emerged as the most critical knowledge areas. Implications:The findings suggest that undergraduate audit education in Vietnam should adopt a blended instructional approach that integrates technical audit content with ethical reasoning, professional judgment, communication skills, and digital competencies. Greater collaboration between universities and practitioners may enhance curriculum relevance and better prepare graduates for professional practice. Originality/Value:This study provides empirical evidence from practicing auditors in a transitional economy, offering practitioner-based insights into audit education that remain under-represented in the international accounting education literature, particularly in the Southeast Asian context. Paper type:Empirical research paper.